Test of a Modular Fault Current Limiter for 220 V Line Using YBCO Coated Conductor Tapes With Shunt Protection - Baldan, Carlos Alberto [UNESP]; Lamas, Jerika S.; Shigue, Carlos Y.; Ruppert Filho, Ernesto (Institute of Electrical and Electronics Engineers (IEEE), 2011)
A modular superconducting fault current limiter (SFCL) consisting of 16 elements was constructed and tested in a 220 V line for a fault current between 1 kA to 7.4 kA. The elements are made up of second generation (2G) YBCO-coated conductor tapes with stainless steel reinforcement. For each element four tapes were electrically connected in parallel with effective length of 0.4 m per element, totaling 16 elements connected in series. The evaluation of SFCL performance was carried out under DC and AC tests. The DC test was performed through pulsed current tests and its recovery characteristics under load current were analysed by changing the shunt resistor value. The AC test performed using a 3 MVA/220 V/60 Hz transformer has shown the current limiting ratio achieved a factor higher than 10 during fault of up to five cycles without conductor degradation. The measurement of the voltage for each element during the AC test showed that in this modular SFCL the quench is homogeneous and the transition occurs similarly in all the elements.
Keywords: Current limiting ratio; superconducting fault current limiter; YBCO coated conductor; YBCO recovery characteristics